Peculiarities of Use of Dancing Exercises in Physical Education of Female High Schoolers - Кравчук, Т. М.; Голівець, К. М. (Physical Education Theory and Methodology, 2015)
The purpose of the research is to ground and develop the methods of the use of dancing exercises at physical training classes in high school and to experimentally verify their effectiveness. Research methods. Theoretical ones: study and analysis of pedagogical, scientific and methodological literature on the problems under research; a complex of empirical research methods: research and experimental work, observations, questionnaires, testing; statistical methods of research and data reduction. Research results. The paper reveals the peculiarities of the use of dancing exercises at physical training classes in high school. It shows that dancing exercises can and must be part of the physical education of high schoolers to develop their strength, flexibility, endurance, coordination abilities and to cultivate movement culture, musicality, dancing abilities and aesthetic taste. The study proves that the use of dancing exercises of classical choreography, rhythmic gymnastics and health-improving aerobics at the physical training classes in high school helps increase the level of development of flexibility, strength and agility.